Processing and microstructural characterisation of AA 1070 and AA 6063 matrix B4Cp reinforced composites - Toptan, Fatih; Kilicarslan, Ayfer; Karaaslan, Ahmet; Cigdem, Mustafa; Kerti, Isil (ELSEVIER SCI LTD, 2010)
Wetting problem between B4C and liquid Al at lower temperatures has to be overcomed for promised mechanical and physical properties, such as high hardness, high wear resistance and stiffness. In the present work, AA 1070 and AA 6063 matrix B4Cp reinforced composites were produced by casting route at 850 degrees C and titanium-containing flux (K2TiF6) was used to overcome the wetting problem between B4C and liquid aluminium metal. AA 6063/B4Cp composite samples were then subjected to solution treatment. The microstructure of matrix/reinforcement interfaces of both as-cast and heat treated samples with or without Ti additions were investigated with SEM studies. The reaction layer was also characterized with EDS analysis and X-ray mapping. It was found from the microstructural observations by high resolution field emission gun SEM (FEG-SEM) that the wetting improved by the formation of very thin TiC and TiB2 reaction layers. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aluminium; Boron carbide; Casting; Composite; Interface; Microstructure; Solution treatment; Titanium; ALUMINUM; PARTICLES; BEHAVIOR; NICKEL; Materials Science